PENGARUH LATIHAN AEROBIK TWO-STEP STOOL TERHADAP FUNGSI PARU PADA REMAJA DENGAN AKTIVITAS FISIK KURANG - Ismail, Frans F D; Sengkey, Lidwina S.; Lolombulan, Julius H (FAKULTAS KEDOKTERAN UNSRAT, 2018)
ABSTRACTObjective: To analyze the extent of two-step stool (TSS) aerobic exercise in improving lung function in adolescents who are less physicaly activity. Method: The study design was an experimental study with one group pretest-posttest design. The subjects were 11 students of class 10th Catholic High School St. Thomas Aquino Manado who met the inclusion criteria and willing to participate in research. All subjects performed an initial evaluation. The treatments were performed TSS aerobic exercise which uses a speed of 60, 70, 80, and 90 steps / minute. Each speed step exercises performed 3x per week. Each week pace increased. Exercise for 4 weeks. Results: Lung Function Test with Spirometry obtained an increase in FVC (p<0.05) and FEV1 (p<0.05) were significant. Conclusion: Two-Step Stool Aerobic exercise improve lung function in adolescents who are less physicaly activity.Keywords: Two-step stool aerobic exercise, lung function, Forced Vital Capacity (FVC), Forced Expired Volume in one second (FEV1).Â ABSTRAKTujuan: Menganalisis sejauh mana latihan aerobik two-step stool (TSS) meningkatkan fungsi paru pada remaja yang beraktivitas fisik kurang. Metode: Desain penelitian adalah penelitian eksperimental dengan one group pretestâ€“posttest design. Subjek penelitian adalah 11 siswa siswi kelas X Sekolah Menengah Atas Katolik St. Thomas Aquino Manado yang memenuhi kriteria inklusi dan bersedia mengikuti penelitian. Semua subjek dilakukan evaluasi awal. Perlakuan yang dilakukan adalah latihan aerobik TSS yang menggunakan kecepatan 60, 70, 80, dan 90 langkah/menit. Tiap kecepatan langkah dilakukan latihan 3x perminggu. Tiap minggu kecepatan langkah dinaikkan. Latihan dilakukan selama 4 minggu. Hasil: Pada Uji Fungsi Paru dengan Spirometri didapatkan peningkatan FVC (p<0,05) dan FEV1 (p<0,05) yang bermakna. Kesimpulan: Latihan aerobik TSS meningkatkan fungsi paru pada remaja yang beraktivitas fisik kurang.Kata kunci: Latihan aerobik two-step stool, fungsi paru, Forced Vital Capacity (FVC), Forced Expired Volume in one second (FEV1).